Air pollution in China: a study of public perception - Yan, Yihong (Kansas State University, 2016)
Air pollution is a serious health and environmental problem. In fact, poor air quality has been linked to numerous diseases and is a significant public health issue related to urban planning. These problems can be clearly seen in urban Chinese cities, most recently with the first ever Red Alert in Beijing China in 2015. In 2015, director Chai Jing developed a documentary depicting the bad effects on health of air pollution in China. However, soon after the release of the film, it was banned. One important finding in the film was the misperception the Chinese people had about the kinds of pollution and the health impacts. Therefore, this study aims to investigate the extent to which Chinese people understand the causes of air pollution and their related health effects. Accordingly, a survey was produced and delivered via Chinese social medium. The survey had three objectives: study the perception of 1) Air quality and the source of air pollution, 2) Health effects if air pollution, and 3) Air pollution and Environmental policies. The results show that 44% Chinese people feel air quality is worse now than a year before, and 72% people feel air pollution has affected their health. One main finding in this study was that younger people took the survey more than older people, as perhaps because they may have started to have a family or become a family; this is significant because air pollution is harmful for children. The other main finding was that 52% people did not know a China Air Pollution and Prevention Law exists.
Keywords: Transportation; Environmental health; Perception; Air pollution; Public awarenessUrban planning